2015
DOI: 10.2355/isijinternational.isijint-2015-125
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Refractory-Steel Interfacial Reaction on the Formation Behavior of Inclusions in Ce-containing Stainless Steel

Abstract: Effect of Ce addition on the interfacial reaction between alumina refractory and 25wt%Cr-20wt%Ni-4wt%Si-0.5wt%Mn stainless steel deoxidized by Al at 1 873 K was investigated to understand the contribution of the refractory-steel reaction to the inclusion evolution processes. The oxygen content markedly decreased by Al deoxidation, followed by a sluggish decrease by Ce addition greater than 0.5 wt%. The Ce content continuously decreased, but the higher the initial Ce content, the lower the Ce-decreasing rate wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 29 publications
2
32
0
Order By: Relevance
“…A similar result was also observed by Katsumata et al in 25 mass% Cr-6 mass% Ni stainless steel [8]. Kwon et al [9,10] investigated the evolution of inclusions in Al-killed stainless steel with Ce addition at 1873 K. Mn(Cr)-silicates were found to be the primary inclusions before Al addition. When Al was added without Ce addition, the initial Mn(Cr)-silicate changed to Al 2 O 3 -rich inclusions.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…A similar result was also observed by Katsumata et al in 25 mass% Cr-6 mass% Ni stainless steel [8]. Kwon et al [9,10] investigated the evolution of inclusions in Al-killed stainless steel with Ce addition at 1873 K. Mn(Cr)-silicates were found to be the primary inclusions before Al addition. When Al was added without Ce addition, the initial Mn(Cr)-silicate changed to Al 2 O 3 -rich inclusions.…”
supporting
confidence: 78%
“…The influence of different REM on the behavior of inclusions at steelmaking temperature has been well investigated [7][8][9][10][11][12]. Dan et al [7] studied the deoxidation characteristic of Al-Ce and Al-Y complex deoxidizers in molten iron.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12] Some side reactions between RE elements and crucibles were also investigated. 13,14) It was proved that RE-As even RE-O-S-As inclusions might form in arsenic RE steels. 15,16) What kinds of inclusions may form greatly depends on the chemical compositions of steel, especially the concentrations of RE, O and S; further, the formation of arsenic inclusions depends to a large extent on RE inclusions.…”
Section: Introductionmentioning
confidence: 99%
“…3,4) Torkamani et al 5) found that rare earth elements could change the interaction between the inclusions and matrix during the solidification process, affecting the microstructural features. Kwon et al 6) reviewed that a decrease in Ce content was attributable to the formation of oxide inclusions, and the inclusion-steel interfacial area could be acted as the preferential site for initiation of pitting corrosion. Arenas et al 7) reported that not only the control of composition, size and morphology of Ce-containing inclusions in steel but also the high seg-regation of Ce element along grain boundaries were highly important for the corrosion behavior of steels.…”
Section: Introductionmentioning
confidence: 99%
“…2 O 3 can be transformed into Ce 2 O 2 S according to the relevant calculations. Similarly, CeS is calculated as follows: @ ......................... (6). ............…”
mentioning
confidence: 99%